38-42 Charles Street, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view of 38-42 Charles Street, located between Chestnut Street to the south and Mount Vernon Street to the north. Signage adorns the facades of the buildings, which face east-northeast towards Charles Street. Automobiles are parked along the curb in front of 38 and 40 Charles Street, and the sidewalk is lined with street lamps. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs